In vitro sensitivity of Corynespora cassiicola isolated from soybean to fungicides and field chemical control of target spot - Teramoto,Adriana (2017)
ABSTRACT Soybean target spot (Corynespora cassiicola) has become an important disease in most soybean growing regions in Brazil. The sensitivity of 34 isolates of C. cassiicola to 11 fungicides was evaluated based on mycelial growth inhibition (boscalid, carbendazim, cyproconazole, fluopyram, fluxapyroxad, prothioconazole and thiophanate-methyl) or spore germination inhibition (azoxystrobin, picoxystrobin, pyraclostrobin and trifloxystrobin). In addition, the efficacy of five fungicides to control target spot was tested in four field trials carried out during three crop seasons: 2011/2012, 2012/2013 and 2013/2014. Fungal isolates were collected from soybean plants in several soybean growing areas in Brazil. The effective concentration of each fungicide to inhibit fungal growth or spore germination by 50% (EC50) was calculated for all isolates. Fluxapyroxad and prothioconazole provided the greatest mycelial growth inhibition and pyraclostrobin led to the lowest spore germination percentage, with the lowest EC50 values. At field experiments, cyproconazole and carbendazim showed target spot control ranging from 26% to 29%. On the other hand, fluxapyroxad and prothioconazole prevented an epidemic of the disease by 45% to 55%, respectively. In general, the efficacy of fungicides in the field reflected the in vitro sensitivity averages. Large sensitivity reduction was detected to benzimidazoles (MBC), indicating that this group of fungicides should no longer be used for target spot control. There was a negative and significant correlation (-0.265) between target spot severity and soybean yield. The pathogen showed variability in sensitivity to the fungicide groups carboxamides (SDHI), triazoles (DMI) and strobilurins (QoI), which denotes a high risk of selection for resistance.